Laskar Jihad’s Response to Mazhab Ambon’s Islamic Thought - Budianto, Muhammad Arief; Candra, Iga Ayu Intan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This research aims to analyze the response of Laskar Jihad to the Islamic thought of Mazhab Ambon, particularly within the context of religious thought dynamics in Ambon. Uniquely, this study offers a new perspective on how Laskar Jihad, as a militant group, responds to the integration of local culture into Islamic teachings. The study explores the application and reception of Mazhab Ambon Islamic teachings in Ambon, as well as their impact on the social and religious life of the local community. The conflict in Ambon, which can be easily triggered due to a lack of interfaith tolerance, prompted Muslim scholars in Maluku to develop the Mazhab Ambon Islamic thought, which integrates Islamic teachings with local culture. This research focuses on the views of Laskar Jihad regarding Mazhab Ambon Islam, which is part of the Islam Nusantara concept, to uncover their perspectives on this integration. Using a descriptive qualitative approach and field study, the research involves interviews with religious leaders, members of Laskar Jihad, and the Ambon community, as well as an analysis of related documents and literature. The study also details the data collection and analysis methods used, providing a comprehensive overview of the research process and findings. The main findings indicate that the majority of Laskar Jihad members reject Mazhab Ambon Islam because they believe it undermines the purity of Islamic teachings. However, the study also reveals how Laskar Jihad’s conservative views can influence reconciliation and peacebuilding efforts in Ambon. By highlighting the social relevance of the Mazhab Ambon concept, which aims to promote tolerance, this research makes a significant contribution to understanding religious dynamics in Ambon and offers solutions for creating harmony in a diverse society.